Estimación del cambio del módulo resiliente de la subrasante por efectos del clima en arcillas blandas del norte de Bogotá (2020)
This research aims to use the different models to obtain the adjustment factor of the resilient modulus, and its verification from direct tests using the equipment of the Colombian School of Engineering, to determine the resilient modulus of the soil different saturation conditions and with this establish its applicability to the design of pavements for Bogotá.